Balance training induces highly task-specific neural plasticity - Giboin, L. S.; Kramer, A.; Hassa, T.; Schönfeld, A.; Dettmers, C.; Gruber, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: There is growing evidence that improvements in performance after short-term balance training occur only in the trained task (Giboin, Gruber, & Kramer, 2015), and it has been suggested that this task-specificity has a neuronal origin. However, task-specific neural plasticity after balance training has not been demonstrated yet. In the present study we tested the hypothesis that learning to walk and balance on a slack-line induces specific neural adaptations only for this task. Methods: We measured the amplitude of H-reflexes in the soleus muscle (SOL) during a trained (slackline) and an untrained balance task (tilt-board) before and after six weeks of slackline training (3 times 30 min per week) in a training group (N=15) as well as in a control group (N=13), which did not train. We established comparable conditions between the tasks and for the pre and post measurements by giving the stimulation during the preparatory phase of the balance task, i.e. just before the foot of the subject touched the balance device. Background EMG of the SOL and tibialis anterior muscle (TA) and the angle of the right knee and ankle were measured at stimulation to ensure comparable conditions. To assess the effect of training on a behavioural level, the number of steps on the slackline and the duration of equilibrium on the tilt-board were measured before and after the training. Results: Three ways ANOVA with mixed design showed: i) a task (p<0.01), time (p<0.01) and group*time effect (p<0.001) on performance. Post hoc tests showed that the increase in performance occurred only for the training group and only for the trained task (slackline, p<0.001). ii) No effect of time for the background EMGs nor the knee and ankle angles at the time of stimulation was detected, indicating comparable conditions for the stimulations pre and post training. A two ways ANOVA with mixed design showed an effect of training on the amplitude of the H post expressed in percentage of the amplitude of the H pre training (task effect, p<0.05). Post hoc paired T tests showed that the H reflex was reduced only in the training group during the slackline task (p<0.05). Conclusion: In line with previous studies we found an increased performance only in the trained task. Only during the trained task we observed a modulation of the H-reflex without any differences in the ankle and knee angles and the background EMGs for the pre vs. the post training measurements. Thus, we assume that the modulation of the H-reflex most probably reflect training-induced neural plasticity. We suggest that the training of a specific balance task, here walking on a slackline, induces plasticity at spinal level, which might, at least in part, explain the specificity of the improvement observed on the behavioural level